2007
DOI: 10.1523/jneurosci.4390-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Dentate Granule Cell Chloride Regulation Enhances Synaptic Excitability during Development of Temporal Lobe Epilepsy

Abstract: GABA A receptor-mediated inhibition depends on the maintenance of intracellular ClϪ concentration ([Cl Ϫ ] in ) at low levels. In neurons in the developing CNS, [Cl Ϫ ] in is elevated, E GABA is depolarizing, and GABA consequently is excitatory. Depolarizing GABAergic synaptic responses may be recapitulated in various neuropathological conditions, including epilepsy. In the present study, rat hippocampal dentate granule cells were recorded using gramicidin perforated patch techniques at varying times (1-60 d) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
255
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(276 citation statements)
references
References 48 publications
18
255
1
2
Order By: Relevance
“…KCC2 dysfunction is thought to contribute to traumatic brain injury, neuropathic pain, and acute stress (10). Consistent with this, deficits in the activity and expression levels of KCC2 develop rapidly in animal models of SE and persist after its termination (11)(12)(13).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…KCC2 dysfunction is thought to contribute to traumatic brain injury, neuropathic pain, and acute stress (10). Consistent with this, deficits in the activity and expression levels of KCC2 develop rapidly in animal models of SE and persist after its termination (11)(12)(13).…”
mentioning
confidence: 75%
“…Consistent with their role in mediating GABAergic inhibition, deficits in the cell surface levels of GABA A Rs and the amplitudes of miniature inhibitory postsynaptic currents are evident in animal models of SE (22)(23)(24). KCC2 deficits are also clear in patients with intractable epilepsy and animal models of seizures (11,13,25). Here we have examined the mechanisms that underlie KCC2 inactivation during neuronal hyperexcitability and whether they contribute to the pathophysiology of SE.…”
Section: Positive Modulation Of Kcc2 Function Upon Inhibition Of Proteinmentioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, we have found that KCC2 immunoreactivity is consistently lower in epileptic rats, in the PC as well as in other parahippocampal regions (de Guzman et al, 2006). A transient decrease in KCC2 expression associated with increased excitability was also described in granule cells of the dentate gyrus, during the first 2 weeks after pilocarpine treatment (Pathak et al, 2007). Upregulation of KCC2 in cultures of CA3 neuronal cells prevents the development of hyperexcitability, whereas the downregulation of KCC2 provokes seizure susceptibility (Zhu et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Because GABA is typically inhibitory in adults but excitatory at an early developmental stage, the shift to depolarizing action of GABA after brain insults indicates a replay of development programs (Payne et al, 2003;Ben-Ari and Holmes, 2005). In the pilocarpine model of TLE, this shift in GABA equilibrium potential (E GABA ) is temporally restricted to the period of epileptogenesis and may constitute a significant mechanism linking injury to the subsequent development of epilepsy (Pathak et al, 2007).…”
Section: Introductionmentioning
confidence: 99%